2019
DOI: 10.1002/sdtp.12971
|View full text |Cite
|
Sign up to set email alerts
|

37‐3: Late‐News Paper: Achieving High Field‐Effect Mobility Exceeding 60 cm2/Vs in IZTO Transistor via Metal‐Assisted Crystallization

Abstract: In this paper, the effects of post annealing on the structural, chemical and electrical properties of tantalum (Ta) capped IZTO films were examined for use as the channel in thin-film transistors (TFTs). The onset crystallization temperature of amorphous IZTO was found to be  700 C, which is not suitable for glass or plastic substrate-based display devices. New crystallization method involving the catalytic Ta capping and subsequent post annealing was proposed for the IZTO material system at a low temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Ito et al recently reported high-mobility IGZO with a Hall mobility of 50 cm 2 /Vs [8]. Other highmobility materials, such as indium-tungsten oxide (IWO), indium-zinc-tin oxide (IZTO), and indium-gallium-zinc-tin oxide (IGZTO), were also reported [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Ito et al recently reported high-mobility IGZO with a Hall mobility of 50 cm 2 /Vs [8]. Other highmobility materials, such as indium-tungsten oxide (IWO), indium-zinc-tin oxide (IZTO), and indium-gallium-zinc-tin oxide (IGZTO), were also reported [9][10][11].…”
Section: Introductionmentioning
confidence: 99%